Química orgánica para estudiantes de ingeniería de minas e ingeniería metalúrgica - Maurelia Gómez, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
Organic Chemistry is usually related to agricultural, pharmaceutical, alimentary, petroleum and derivate industries among others. However, the use of organic substances in other different industrial fields, like mining and metallurgy has increased and it is hoped that this increment will go on in the future. In this paper, a brief review of this kind of substances was realized. Besides, an Organic Chemistry Program for Mining and Metallurgy Engineering students is proposed.